Psychosocial Education for Families in Caring for Patients with Schizophrenia: A Systematic Review - Pires, Alexandra Maria; Lesmana, Cokorda Bagus Jaya (Chakra Brahmanda Lentera Institute, 2026)
Background: Schizophrenia is a chronic mental disorder that significantly impacts both patients and their families. Psychosocial education for families plays a crucial role in improving caregivers’ knowledge, reducing burden, and enhancing patient outcomes. This systematic literature review examines studies on family psychoeducation interventions for schizophrenia, focusing on their effectiveness and implementation challenges. Methods: This systematic review followed PRISMA guidelines. We searched Google Scholar, Scopus, Web of Science, and Crossref for peer-reviewed English-language articles from 2003 to 2023, using Boolean operators and keywords such as “family psychoeducation,” “schizophrenia,” and “caregiver burden.” Two reviewers independently screened and extracted data to ensure accuracy and reduce bias. Results: The review includes 15 studies published between 2003 and 2023 that analyse various psychoeducational approaches, study designs, and outcomes. Findings indicate that family psychoeducation significantly reduces caregiver burden, improves family cohesion, and enhances patients’ symptom management and relapse prevention. However, despite its proven effectiveness, the implementation of psychoeducation remains inconsistent due to barriers such as limited resources, lack of structured programs, and cultural variations. Conclusion: The review emphasises the need to integrate psychoeducation into routine mental health services and to train healthcare providers to deliver structured, evidence-based interventions. Future research should explore digital-based psychoeducation to improve accessibility and sustainability. Strengthening family psychoeducation can lead to better patient care, reduced stigma, and improved quality of life for both patients and caregivers